2017
DOI: 10.3390/ijms18081618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Co-Occurring Mutations in Patients with RUNX1-Mutated Acute Myeloid Leukemia

Abstract: (1) Runt-related transcription factor 1 (RUNX1) mutations in acute myeloid leukemia (AML) are often associated with worse prognosis. We assessed co-occurring mutations, response to therapy, and clinical outcomes in patients with and without mutant RUNX1 (mRUNX1); (2) We analyzed 328 AML patients, including 177 patients younger than 65 years who received intensive chemotherapy and 151 patients >65 years who received hypomethylating agents. RUNX1 and co-existing mutations were identified using next-generation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…In addition, unsatisfactory response rates and survival have been reported for conventional chemotherapy in patients with adverse cytogenetic risk or high-risk molecular mutations, such as TP53 (refs. 8 10 ). Elderly patients with high-risk features and poor performance status have induction-related mortality rates in the range of 15–30% (refs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unsatisfactory response rates and survival have been reported for conventional chemotherapy in patients with adverse cytogenetic risk or high-risk molecular mutations, such as TP53 (refs. 8 10 ). Elderly patients with high-risk features and poor performance status have induction-related mortality rates in the range of 15–30% (refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, we observed that AML-MRC with RUNX1 mut is associated with inferior OS compared to AML with RUNX1 mut . This observation is clinically important since poor treatment response and inferior survival outcome associated with RUNX1 mut could be further compromised in AML-MRC patients [21,22]. Although CPX-351 was recently approved as a front-line therapy in AML-MRC patients and hypomethylating agents are commonly used in AML patients who are not eligible for the intensive chemotherapy [23][24][25][26][27], there is still lack of data regarding the optimal treatment in this unique group of AML-MRC with RUNX1 mut patients.…”
Section: Discussionmentioning
confidence: 99%
“…AML with mutated RUNX1 is provisional entity in the new 2016 WHO classification. RUNX1 mutations are present in about 10% of AML, more frequent in older male patients and patients with wildtype NPM1 and CEBPA [29]. There is an association of RUNX1 mutation and immature morphology (minimally differentiated AML/M0 FAB).…”
Section: Molecular Markers With Proven Prognostic Significancementioning
confidence: 99%